Strategi Bisnis Indomaret Dalam Memasuki Pasar Global - Niken Ken Solahudin, Sorga; Hanafi Labay, Muhamad; Rikki, Mario; Zein Saleh, Mohamad (Research and Community Service UNIVERSITAS KALBIS, 2025)
Indomaret's business strategy in entering the global market must rely on a holistic approach that includes market analysis, product adaptation, strategic partnerships, digital innovation, brand development, and adherence to sustainability principles. The purpose of this study is to identify the internal and external factors that influence Indomaret’s readiness to expand into the global market, determine the business strategies that can be applied for competition and adaptation in international markets, and understand the role of innovation, partnerships, and local cultural adaptation in supporting Indomaret’s global expansion success. The method used is literature study. The results of this study indicate that Indomaret's success in expanding into global markets is largely determined by the synergy between innovation, strategic partnerships, and adaptation to local cultures. Innovation enables Indomaret to remain relevant and competitive amid changing trends and international consumer needs, particularly through the use of technology, appropriate product development, and digitalized services.